Secondary basal cell carcinoma of scalp after radiotherapy: A case report. Issue 36 (September 2018) - Chen, Frank; Yang, Sheau-Fang; Chen, Chien-Hung; Lieu, Ann-Shung; Cheng, Shih-Tsung; Huang, Ming-Yii; Lee, Hsin-Hua
Abstract: Rationale: Radiotherapy (RT) is widely used for both malignant and benign tumors in order to reduce the risk of recurrence, to promote tumor control, and to improve survival. However, there have been studies reported that RT is also a risk factor of secondary cancer. Very few cases of secondary malignancy after RT to high grade brain cancer have been reported due to short survival of this disease, and most RT-induced malignancies presented with sarcomatous histology. Here we present a patient with basal cell carcinoma (BCC) 14 years after RT to his brain. Patient concerns: A 28-year-old man without any underlying disease had suffered from left side weakness and clonic-tonic seizures for 12 days. Diagnoses: His brain images showed a tumor in the right frontal lobe. The pathologic report confirmed anaplastic astrocytoma (WHO Grade III). Interventions: After craniotomy and tumor biopsy, RT was delivered. Fourteen years later, a gray-colored skin papule was noted in the previously irradiated area. The scalp biopsy revealed BCC. The scalp BCC was adequately resected. He then suffered from brain tumor recurrence and received further craniotomy for three times combined with chemotherapy with temozolomide. Outcomes: After treatment, follow-up brain images showed that the disease was under control. There was no neurological sequela. For scalp BCC, no skin tumor recurrence has been noted to date after the resection 14 years after initial RT. He has survived for more than 26 years since his initial diagnosis of anaplastic astrocytoma, and more than 12 years from the diagnosis of scalp BCC. Lessons: Notwithstanding the risk of radiation-induced skin cancer, RT contributed to this patient's survival. The possible late adverse events should be informed to the patients.